PV/Battery Hybrid Energy System via a Double Input DC/DC Converter For Dynamic Loads - Tavlasoglu, Yakup; Akar, Furkan; Vural, Bulent (IEEE, 2014)
In this work, the utilization of a Photovoltaic (PV) array and a battery pack in parallel via a double input DC/DC converter including a coupled inductor is reported. The dynamic performance of this proposed hybrid energy system is analyzed in detail through the switching model created in MATLAB (R) Simulink (R) environment by using PLECS (R) power components under different solar irradiance and demanded load levels.
Keywords: DC/DC converters; double input converters; photovoltaic systems; solar energy; hybrid systems; Li-Ion battery; coupled inductor; POINT TRACKING CONTROL; Engineering